2021
DOI: 10.1371/journal.pone.0247171
|View full text |Cite
|
Sign up to set email alerts
|

How alginate properties influence in situ internal gelation in crosslinked alginate microcapsules (CLAMs) formed by spray drying

Abstract: Alginates gel rapidly under ambient conditions and have widely documented potential to form protective matrices for sensitive bioactive cargo. Most commonly, alginate gelation occurs via calcium mediated electrostatic crosslinks between the linear polyuronic acid polymers. A recent breakthrough to form crosslinked alginate microcapsules (CLAMs) by in situ gelation during spray drying (“CLAMs process”) has demonstrated applications in protection and controlled delivery of bioactives in food, cosmetics, and agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The root-mean-square end-to-end distance of alginate with an average molecular weight of 28 200 and a high G/M ratio (G/M = 1.8) was calculated as 48 nm . The alginate used in this study of molecular weight of 172 800 ± 458 was approximately 6-fold larger. Taken together, we surmise that the gelatin–alginate matrix formed in this study could be envisioned as multiple flexible, smaller gelatin polymers crosslinking extended alginate polymers.…”
Section: Discussionmentioning
confidence: 98%
“…The root-mean-square end-to-end distance of alginate with an average molecular weight of 28 200 and a high G/M ratio (G/M = 1.8) was calculated as 48 nm . The alginate used in this study of molecular weight of 172 800 ± 458 was approximately 6-fold larger. Taken together, we surmise that the gelatin–alginate matrix formed in this study could be envisioned as multiple flexible, smaller gelatin polymers crosslinking extended alginate polymers.…”
Section: Discussionmentioning
confidence: 98%
“…A vast majority of studies related to alginate gelation, structure, and application are based on alginate gel particles measurements ranging between >1 mm (macro), 0.2–1000 µm (micro), and <0.2 µm (nano), containing calcium ions as the most frequently used cross-linking agent [ 13 , 14 ]. The structural analysis has revealed that divalent and trivalent cations are able to form a complex with the G-units of two alginate linear polymer chains, forming a cooperative egg-box structure; thereby, two linear chains of polymer are linked by a cross-link [ 15 , 16 , 17 ]. The naturally occurring alginate’s affinity for divalent cations differ in the following order: Pb > Cu > Cd >Ba > Sr > Ca > Co, Ni, Zn > Mn [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A vast majority of alginate particles exist as spheres or beads, synthesized by either internal or external gelation [ 16 , 37 , 38 ]. However, the formation of alginate nanogels is less common in comparison with nanoparticles of other synthetic polymers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The alginate type and source can impact properties such as particle size and the extent of cross-linking. 13,14 As a process parameter, spray dryer feed viscosities modulated by the alginate source have been shown to impact CLAMs properties. 13,14 In this study, two commercially sourced alginates were compared on the basis of the resulting viscosities when dissolved in water (high-viscosity (HV) and low-viscosity (LV) alginates).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 As a process parameter, spray dryer feed viscosities modulated by the alginate source have been shown to impact CLAMs properties. 13,14 In this study, two commercially sourced alginates were compared on the basis of the resulting viscosities when dissolved in water (high-viscosity (HV) and low-viscosity (LV) alginates). The HA-CLAMs were water insoluble and exhibited unique release characteristics.…”
Section: Introductionmentioning
confidence: 99%